Recycled polymer compositions and methods thereof

JP2024510983A5Inactive Publication Date: 2025-03-14BRASKEM SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023555620
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-09-01
Filing Date
2022-03-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The permanent crosslinked polymer networks in EVA foams, such as those used in shoe midsoles and automotive applications, cannot be effectively recycled or reprocessed due to their inability to melt or dissolve, leading to significant environmental waste and increased manufacturing costs.

Method used

A method involving the use of a catalyst to convert crosslinked polymers into dynamically crosslinked polymers during melt processing, allowing for the formation of a polymer composition that can be reprocessed by mixing crosslinked and non-crosslinked polymers at elevated temperatures, thereby replacing permanent covalent bonds with dynamic crosslinks.

Benefits of technology

Enables the reprocessing of crosslinked polymers, reducing waste and lowering manufacturing costs while maintaining or improving the properties of the resulting polymer composition, allowing for the reuse of scrap materials in applications like shoe midsoles and automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The method includes processing a crosslinked polymer and a catalyst to form a vitrimer during a melt processing operation, the crosslinked polymer comprising at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof. The method can include mixing the crosslinked polymer, the catalyst, and a non-crosslinked polymer at a temperature higher than the processing temperature of the non-crosslinked polymer to form a polymer composition, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises a vinyl ester, a C2-C12 olefin, and combinations thereof, and the crosslinked polymer is present in an amount of at least 15% by weight based on the combined total of the crosslinked polymer and the non-crosslinked polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to recycled polymer compositions and methods thereof. [Background technology]

[0002] Ethylene vinyl acetate (EVA) is widely used to produce foams that are lightweight and have very high toughness, high elasticity, and high compression set. EVA foams are used in demanding applications such as running shoe midsoles, as well as automotive and construction applications such as interior padding, carpet underlay, gaskets, etc. The polymer structure required for EVA shoe midsoles and other foam applications is a three-dimensional network, which is created by cross-linking adjacent polymer molecules.

[0003] Dynamically crosslinked polymer networks offer a balance of performance, properties, and durability. However, the same properties that make permanent networks excellent candidates in the materials selection for high performance foams pose difficult environmental challenges. Once formed, these network structures do not melt, flow, or dissolve to enable the use of traditional reprocessing or recycling methods.

[0004] The industrial scrap generated during the processing of permanent networks cannot be fully reintroduced into the manufacturing process as secondary raw material, and only a small portion of the industrial waste from crosslinked polymers is ground and reintroduced as filler. Similarly, end-of-life parts made from permanently crosslinked polymers have limited recycling options, e.g. energy-intensive grinding operations that produce only low-value materials. As a result, a significant proportion of industrial scrap and used parts accumulate as environmental waste.

[0005] In addition to the significant environmental impact, the fact that covalently crosslinked EVA foam cannot be reprocessed by melting represents a significant cost to manufacturers, and the large amount of waste limits the utilization rate of the primary material and creates costs for waste disposal. Summary of the Invention [Problem to be solved by the invention]

[0006] There is a need for technology that allows for the reprocessing of crosslinked polymers, particularly crosslinked EVA foam.

[0007] [overview] This Summary is provided to introduce a selection of concepts that are further described below in the Detailed Description. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter. [Means for solving the problem]

[0008] In one aspect, embodiments disclosed herein relate to a method comprising processing a crosslinked polymer and a catalyst to form a dynamic crosslinked polymer during a melt processing operation, the crosslinked polymer comprising at least one monomer selected from vinyl esters, C2 to C12 olefins, and combinations thereof.

[0009] In another aspect, embodiments disclosed herein relate to a method comprising mixing a crosslinked polymer, a catalyst, and a non-crosslinked polymer at a temperature greater than the processing temperature of the non-crosslinked polymer to form a polymer composition, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, and wherein the crosslinked polymer is present in an amount of at least 15% by weight based on the combined total of the crosslinked polymer and the non-crosslinked polymer.

[0010] In another aspect, embodiments disclosed herein relate to a thermoplastic polymer composition produced by processing a crosslinked polymer and a catalyst during a melt processing operation to form a dynamically crosslinked polymer, the crosslinked polymer comprising at least one monomer selected from vinyl esters, C2 to C12 olefins, and combinations thereof.

[0011] In another aspect, embodiments disclosed herein relate to a thermoplastic polymer composition made by combining a crosslinked polymer, a catalyst, and a non-crosslinked polymer at a temperature greater than the processing temperature of the non-crosslinked polymer to form a polymer composition, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, and the crosslinked polymer is present in an amount of at least 15% by weight based on the combined weight of the crosslinked polymer and the non-crosslinked polymer.

[0012] In yet another aspect, embodiments disclosed herein relate to an article comprising a thermoplastic polymer composition produced by processing a crosslinked polymer and a catalyst during a melt processing operation to form a dynamically crosslinked polymer, wherein the crosslinked polymer comprises at least one monomer selected from vinyl esters, C2 to C12 olefins, and combinations thereof.

[0013] In yet another aspect, embodiments disclosed herein relate to an article comprising a thermoplastic polymer composition produced by combining a crosslinked polymer, a catalyst, and a non-crosslinked polymer at a temperature greater than the processing temperature of the non-crosslinked polymer, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, and wherein the crosslinked polymer is present in an amount of at least 15% by weight relative to the combined weight of the crosslinked polymer and the non-crosslinked polymer.

[0014] In yet another aspect, embodiments disclosed herein relate to a method of making a printed article comprising sequentially printing layers of a polymer composition produced by processing a crosslinked polymer and a catalyst during a melt processing operation to form a dynamically crosslinked polymer, wherein the crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof.

[0015] In yet another aspect, embodiments disclosed herein relate to a method of making a printed article comprising sequentially printing layers of a polymer composition made by combining a crosslinked polymer, a catalyst, and a non-crosslinked polymer at a temperature higher than the processing temperature of the non-crosslinked polymer, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, and wherein the crosslinked polymer is present in an amount of at least 15% by weight relative to the combined weight of the crosslinked polymer and the non-crosslinked polymer.

[0016] In yet another aspect, embodiments disclosed herein relate to a method of reprocessing a polymer composition comprising reprocessing a polymer composition produced by processing a crosslinked polymer and a catalyst during a melt processing operation to form a dynamically crosslinked polymer, the crosslinked polymer comprising at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, the reprocessing being at a temperature above the melting or softening temperature of the thermoplastic polymer, and after the reprocessing, the polymer composition maintains at least 40% of its initial storage modulus plateau above its melting temperature as measured by dynamic mechanical analysis compared to the polymer composition prior to the reprocessing.

[0017] In yet another aspect, embodiments disclosed herein relate to a method of reprocessing a polymer composition, the method comprising: reprocessing a polymer composition made by combining a crosslinked polymer, a catalyst, and a non-crosslinked polymer to form a polymer composition at a temperature above the processing temperature of the non-crosslinked polymer, wherein each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2-C12 olefins, and combinations thereof, and the crosslinked polymer is present in an amount of at least 15% by weight based on the total of the crosslinked polymer and the non-crosslinked polymer. The reprocessing is at a temperature above the melting or softening temperature of the thermoplastic polymer, and after the reprocessing, the polymer composition maintains at least 40% of its initial storage modulus plateau above its melting temperature as measured by dynamic mechanical analysis compared to the polymer composition prior to the reprocessing.

[0018] Other aspects and advantages of the claimed subject matter will become apparent from the following description and the appended claims. [Brief description of the drawings]

[0019] [Figure 1] Figure 1 shows the DMA test results. [Diagram 2]Figure 2 shows the DMA test results. [Diagram 3] Figure 3 shows the DMA test results. [Figure 4] FIG. 4 shows the thermal response of various samples after reactive extrusion. [Diagram 5] FIG. 5 shows the thermal response of various samples after reactive extrusion. [Figure 6] FIG. 6 shows the viscoelastic response at 170°C. [Figure 7] FIG. 7 shows the viscoelastic response at 170°C. [Figure 8] FIG. 8 shows the viscoelastic response at 170°C. [Figure 9] FIG. 9 shows the viscoelastic response at 170°C. [Figure 10] Figures 10A and 10B show the stress relaxation results for various samples, with Figure 10A demonstrating the robustness of the stress relaxation behavior and Figure 10B showing the normalized stress relaxation. The horizontal line in the normalized graph indicates where the normalized elastic modulus reaches the value of 1 / e. [Figure 11] Figures 11A and 11B show the stress relaxation results for various samples, with Figure 11A demonstrating the robustness of the stress relaxation behavior and Figure 11B showing the normalized stress relaxation. The horizontal line in the normalized graph indicates where the normalized elastic modulus reaches the value of 1 / e. [Figure 12] Figures 12A and 12B show the stress relaxation results for various samples, with Figure 12A demonstrating the robustness of the stress relaxation behavior and Figure 12B showing the normalized stress relaxation. The horizontal line in the normalized graph indicates where the normalized elastic modulus reaches the value of 1 / e. [Figure 13] FIG. 13 shows the results of reprocessing the samples. [Figure 14] FIG. 14 shows the results of reprocessing the samples. [Figure 15] FIG. 15 shows the results of reprocessing the samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The embodiments disclosed herein relate to polymer compositions and methods of forming such polymer compositions. The polymer compositions can be formed by a reprocessing process of a crosslinked polymer in the presence of a catalyst to form a dynamically crosslinked polymer. In particular, such crosslinked polymers that undergo reprocessing processes can include polymers formed from olefins, vinyl esters, or combinations thereof. The embodiments may also include a non-crosslinked polymer combined with a crosslinked polymer and a catalyst such that the resulting polymer composition can have a multiphase structure.

[0021] Dynamic crosslinked polymers (dynamically crosslinked polymers) refer to dynamic crosslinked systems, also called "ionic or covalent adaptable networks", which are a type of chemically crosslinked polymers in which external stimuli (such as temperature, stress, pH, etc.) can trigger bond exchange reactions, thereby allowing the network topology to change while the number of bonds and crosslinks remains constant. The dynamic bonds present in the dynamically crosslinked polymers can undergo coupled exchange reactions, thereby allowing the network topology to change, and the material to relax and flow, although the total number of bonds remains constant in time and does not change at all times and at all temperatures. Dynamically crosslinked polymers exhibit the properties of crosslinked materials (high chemical resistance, excellent mechanical properties) at ambient temperatures, while they can be processed or reprocessed (reprocessed) as thermoplastic materials at elevated temperatures.

[0022] According to one or more embodiments, the non-reprocessable crosslinked polymer can be mixed or processed with a catalyst and any non-crosslinked polymer. Such mixing or processing can be done, for example, in an extruder, to convert the crosslinked polymer into a dynamically crosslinked polymer, thereby converting the permanent covalent crosslinks in the crosslinked polymer into an adaptable network. Advantageously, embodiments of the present disclosure can allow for increased incorporation of scrap or recycled crosslinked materials into the polymer composition, thereby reducing the amount of waste. Furthermore, it is contemplated that such polymer compositions incorporating highly crosslinked polymers can still have desired properties, such as tensile elongation at break, tensile stress at break, flexural modulus, and / or Izod impact resistance, that are desirable for a particular application, for example, by modifying the amount, type, and properties of the non-crosslinked polymer. In one or more embodiments, the polymer composition (when crosslinked) can have one or more properties at least equal to or greater than the properties of the crosslinked polymer alone. However, it is also contemplated that in some applications, it may be acceptable (or desirable) for the properties to be lower than the properties of the crosslinked polymer alone. Furthermore, articles formed from the polymeric compositions may have comparable stress and elongation at break, hardness, compression set, impact strength, density, tear strength, elasticity, abrasion resistance, etc. to those formed from non-crosslinked polymers without the dynamically crosslinked polymer, i.e., the inclusion of the dynamically crosslinked polymer within a matrix of non-crosslinked polymer does not adversely affect the properties of the article.

[0023] <Cross-linked polymer> As discussed, embodiments of the present disclosure may allow for increased incorporation of pre-crosslinked polymers incorporated therein.

[0024] In one or more embodiments, the crosslinked polymer comprises at least one monomer selected from C2-C12 olefins, such as ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene; vinyl esters, such as vinyl acetate, vinyl propionate, vinyl laurate, vinyl versatate ester, and the like; and combinations thereof. Thus, for example, it is contemplated that the crosslinked polymer may include polymers such as polyethylene, including high density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene; polypropylene, ethylene and / or propylene-based copolymers, such as ethylene / propylene copolymer, ethylene vinyl acetate, ethylene propylene diene monomer (EPDM), ethylene / styrene copolymer, ethylene / acrylate copolymer; and poly(vinyl acetate). In copolymers of olefins and vinyl ester(s), it is contemplated that the vinyl ester(s) may be present as a comonomer in amounts ranging from lower limits of 1, 5, 10, 15, 18, or 20% to upper limits of 25, 40, 60, or 80%. In one or more particular embodiments, vinyl acetate may be used as a monomer or comonomer.

[0025] It is also contemplated that the crosslinked polymer may include branched vinyl ester comonomers, either in combination with ethylene alone to form a copolymer or in combination with ethylene and vinyl acetate to form a terpolymer. Such copolymers and terpolymers are described in U.S. Patent Application Serial No. 17 / 063,488, which is incorporated herein by reference in its entirety. For example, such branched vinyl ester monomers may include monomers having the following general structure (I): [ka] In the formula, R 4 and R 5has a total of 6 or 7 carbon atoms. However, it is contemplated that other branched vinyl esters described in U.S. Patent Application Serial No. 17 / 063,488 can be used.

[0026] When referring to crosslinked polymers forming the polymer compositions described herein, it is intended that the polymers are crosslinked (including permanent covalent bonds) prior to the addition of the catalyst, and following processing in the presence of the catalyst, the permanent crosslinks of the crosslinked polymer are converted into a dynamically crosslinked system, i.e., a dynamically crosslinked polymer.

[0027] In one or more embodiments, the crosslinked polymer is pre-processed, thus indicating that the crosslinked polymer has undergone one or more prior processing steps leading to the formation of covalent crosslinks before being mixed / processed with the catalyst, such as, but not limited to, crosslinking in an autoclave, in a hot air tunnel, UV irradiation, foaming, melt processing, injection molding, or compression molding. Furthermore, in one or more embodiments, the crosslinked polymer may be pre-compounded with one or more additives or fillers, or alternatively, may be a crosslinked polymer without such additional components. Thus, in one or more embodiments, the crosslinked polymer is a recycled resin, such as post-consumer resin, post-industrial resin, or scrap material that cannot be used for reprocessing due to the presence of covalent crosslinks. Generally, once such crosslinks are formed, these network structures do not melt, flow, or dissolve to allow the use of conventional reprocessing or recycling methods. For example, in one or more specific embodiments, the crosslinked polymer may be scrap from the molding of EVA midsole shoes, or recycled shoe soles. Thus, for example, such pre-processed cross-linked polymer may be previously molded or extruded, after which the sprues, runners, flash, rejected parts, etc. are ground or chopped and mixed with a catalyst to convert the cross-linked polymer into a dynamic cross-linked network.

[0028] It is further understood that crosslinked polymers may originate from other industrial manufacturing processes as scrap or recycled material that cannot be reused due to the presence of crosslinks. However, the present embodiments overcome the technical barriers associated with the permanent nature of the covalent bonds that hold crosslinked polymer networks together by replacing permanent crosslinks with a new class of vitrimers to generate polymer networks that can undergo topological rearrangement under certain environmental conditions.

[0029] In one or more embodiments, the crosslinked polymer, e.g., scrap polymer, comprises at least 5%, 10%, 15%, at least 20%, at least 25%, or at least 50% by weight of the polymer composition, including compositions consisting only of the crosslinked polymer, catalyst, and optionally one or more non-polymeric additives, i.e., polymer compositions that do not include non-crosslinked polymer.

[0030] <Catalyst> In one or more embodiments, the crosslinked polymer is combined with a catalyst that promotes the exchange reaction for dynamic crosslinking described above. In one or more embodiments, the catalyst is a metal salt selected from the group consisting of metal salts, metal oxides, metal alkoxides, metal acrylates, metal acetylacetonates, metal hydrides, metal halides, and metal hydroxides. Such metals include basic metals, alkaline earth metals, transition metals, and rare earth metals, such as zinc, tin, molybdenum, vanadium, copper, tungsten, magnesium, cobalt, calcium, titanium, potassium, lithium, sodium, nickel, aluminum, lead, iron, and zirconium.

[0031] In one or more embodiments, the catalyst is selected from borates, diamines, diols, diacids, dianhydrides, and combinations thereof. In one or more embodiments, these catalysts may be used in combination with the metal salt catalysts described above.

[0032] In one or more embodiments, the catalyst is present in an amount greater than 2 mole percent relative to the crosslinked polymer. It is contemplated that it may be desirable to add a catalyst in an amount sufficient to create dynamic crosslinks within the crosslinked polymer, as well as the non-crosslinked polymer, to form crosslinks between the two.

[0033] <Non-crosslinked polymer>

[0034] In one or more embodiments, the non-crosslinked polymer comprises at least one monomer selected from C2-C12 olefins, such as ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, and the like; vinyl esters, such as vinyl acetate, vinyl propionate, vinyl laurate, vinyl versatate ester, and the like; and combinations thereof. Thus, for example, it is contemplated that the non-crosslinked polymer may include polymers such as polyethylene, including high density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene; polypropylene, ethylene and / or propylene-based copolymers, such as ethylene / propylene copolymers, ethylene vinyl acetate, ethylene propylene diene monomer (EPDM), ethylene / styrene copolymers, ethylene / acrylate copolymers; and poly(vinyl acetate). In the copolymer of olefin and vinyl ester(s), the vinyl ester(s) is present as a comonomer in an amount ranging from a lower limit of 5, 10, 15, 18, or 20% to an upper limit of 25, 40, 60, or 80%. In one or more particular embodiments, vinyl acetate can be used as a monomer or comonomer. The ethylene vinyl acetate can have a melt flow ranging from 0.1 to 300 g / 10 min, measured at 190° C. and 2.16 kg according to ASTM D1238.

[0035] It is also envisioned that the non-crosslinked polymer may include branched vinyl ester comonomers (either with ethylene alone to form a copolymer, or with ethylene and vinyl acetate to form a terpolymer). Such copolymers and terpolymers are described in U.S. Patent Application Serial No. 17 / 063,488, which is incorporated herein by reference in its entirety. For example, such branched vinyl ester monomers may include monomers having the following general structure (I): [ka] In the formula, R 4 and R 5 has a total of 7 carbon atoms.

[0036] In one or more embodiments, the non-crosslinked polymer comprises less than 85%, less than 80%, less than 75%, or less than 50% by weight of the polymer composition.

[0037] Upon combining the crosslinked polymer, catalyst, and non-crosslinked polymer, the resulting polymer composition may be multiphasic having a matrix phase of non-crosslinked polymer with a dispersed phase of dynamically crosslinked polymer present. It is further envisioned that depending on the mixing or processing conditions, dynamically crosslinked polymer may form on the surface of the dispersed phase, in the matrix phase, and at the interface between the two phases.

[0038] <Optional Additives>

[0039] The polymeric compositions of the present disclosure may also include, in addition to the crosslinked polymer, catalyst, and optionally non-crosslinked polymer, one or more optional additives, such as, but not limited to, fillers, blowing agents, foaming accelerators, curing agents, crosslinking agents, free radical initiators, elastomers, plasticizers, processing aids, mold release agents, lubricants, dyes, pigments, antioxidants, light stabilizers, flame retardants, or other additives to alter the balance of stiffness and elasticity in the polymeric composition, such as fibers, fillers, and other reinforcing elements. In some embodiments, one or more of such additives may be added during the initial mixing or melt processing of the crosslinked polymer and catalyst, while in one or more embodiments, one or more of such additives may be incorporated in a subsequent process step.

[0040] The polymeric composition according to the present disclosure may include one or more foaming accelerators (also known as kickers) that enhance or initiate the action of the foaming agent by lowering the associated activation temperature. For example, a foaming accelerator may be used if the selected foaming agent reacts or decomposes at temperatures above 170° C., such as 220° C. or higher, and the surrounding polymer decomposes when heated to the activation temperature. The foaming accelerator may include any suitable foaming accelerator capable of activating the selected foaming agent. In one or more embodiments, suitable foaming accelerators include cadmium salts, cadmium-zinc salts, lead salts, lead-zinc salts, barium salts, barium-zinc (Ba-Zn) salts, zinc oxide, titanium dioxide, triethanolamine, diphenylamine, sulfonated aromatic acids, and salts thereof, and the like. The polymeric composition according to certain embodiments of the present disclosure may include zinc oxide as one of the one or more foaming accelerators. In some embodiments, a foaming accelerator may be included in the elastomeric EVA composition in addition to or instead of the polymeric composition itself.

[0041] The polymer composition according to the present disclosure can include one or more blowing agents to produce the expanded polymer composition and the foam. The blowing agents can include solid, liquid, or gas blowing agents. In embodiments utilizing a solid blowing agent, the blowing agent can be combined with the polymer composition as a powder or granules.

[0042] Blowing agents according to the present disclosure may include chemical blowing agents that decompose at polymer processing temperatures to release a blowing gas, such as N2, CO, CO2, etc. Examples of chemical blowing agents may include organic blowing agents, which may include hydrazines, such as toluenesulfonylhydrazine, hydrazides, such as oxydibenzenesulfonylhydrazide, diphenyloxide-4,4'-disulfonic acid hydrazide, and the like, nitrates, azo compounds, such as azodicarbonamide, cyanovaleric acid, azobis(isobutyronitrile), and N-nitroso compounds, and other nitrogen-based materials, as well as other compounds known in the art.

[0043] Inorganic chemical foaming agents can include carbonates such as sodium hydrogen carbonate (sodium bicarbonate), sodium carbonate, potassium bicarbonate, potassium carbonate, ammonium carbonate, etc., which may be used alone or in combination with weak organic acids such as citric acid, lactic acid, or acetic acid.

[0044] The polymer composition according to the present disclosure may contain one or more plasticizers to adjust the physical properties and processability of the composition. In some embodiments, the plasticizer according to the present disclosure may be bis(2-ethylhexyl)phthalate (DEHP), diisononyl phthalate (DINP), bis(n-butyl)phthalate (DNBP), butyl benzyl phthalate (BZP), diisodecyl phthalate (DIDP), di-n-octyl phthalate (DOP or DNOP), di-o-octyl phthalate (DIOP), diethyl phthalate (DEP), diisobutyl phthalate (DIBP), di-n-hexyl phthalate, trimethyl trimellitate (TMTM), tri-(2-ethylhexyl) trimellitate (TEHTM-MG), tri(n-octyl, n-decyl) trimellitate, tri(heptyl, nonyl) trimellitate, n-octyl trimellitate, bis(2-ethyl) adipate, Polyesters of adipic acid such as diethyl ether (DEHA), dimethyl adipate (DMD), monomethyl adipate (MMAD), dioctyl adipate (DOA), dibutyl sebacate (DBS), VIERNOL, dibutyl maleate (DBM), diisobutyl maleate (DIBM), benzoic acid esters, epoxidized soybean oil, n-ethyl toluene sulfonamide, n-(2-hydroxypropyl)benzenesulfonamide, n-(n-butyl)benzenesulfonamide, tricresyl phosphate (TCP), tributyl phosphate (TBP), glycols / polyesters, triethylene glycol dihexanoate (3gh), tetraethylene glycol diheptanoate, polybutenes, acetylated monoglycerides;Included may be one or more of alkyl citrates, triethyl citrate (TEC), acetyl triethyl citrate, tributyl citrate, acetyl tributyl citrate, trioctyl citrate, acetyl trioctyl citrate, trihexyl citrate, acetyl trihexyl citrate, butyryl trihexyl citrate, trihexyl o-butyryl citrate, trimethyl citrate, alkyl sulfonic acid phenyl esters, 2-cyclohexanedicarboxylic acid diisononyl esters, nitroglycerin, butanetriol trinitrate, dinitrotoluene, trimethylolethane trinitrate, diethylene glycol dinitrate, triethylene glycol dinitrate, bis(2,2-dinitropropyl) formal, bis(2,2-dinitropropyl) acetal, 2,2,2-trinitroethyl 2-nitroxyethyl ether, mineral oil, and other plasticizers and polymeric plasticizers. In certain embodiments, one of the one or more plasticizers can be a mineral oil;

[0045] The polymeric compositions according to the present disclosure may include one or more inorganic fillers, such as talc, glass fiber, marble dust, cement dust, clay, carbon black, feldspar, silica or glass, fumed silica, silicates, calcium silicate, silicate powder, glass microspheres, mica, metal oxide particles and nanoparticles, such as magnesium oxide, antimony oxide, zinc oxide, inorganic salt particles and inorganic nanoparticles, such as barium sulfate, wollastonite, alumina, aluminum silicate, titanium oxide, calcium carbonate, polyhedral silsesquioxane oligomers (POSS), recycled EVA, and other recycled rubber. As defined herein, recycled EVA may be derived from reground material that has been subjected to at least one processing method, such as molding or extrusion, after which sprues, runners, flash, rejected parts, etc. are ground or shredded. According to embodiments of the present disclosure, such recycled materials are combined with a catalyst to form the polymer compositions described herein having a dynamically crosslinked network, although it is also contemplated that additional recycled EVA or other polymers can be added as fillers in a subsequent compounding step.

[0046] <Processing>

[0047] In one or more embodiments, the crosslinked polymer, catalyst, and optionally non-crosslinked polymer are subjected to a melt processing operation to form a dynamically crosslinked polymer and the claimed polymer composition. Specifically, the crosslinked polymer, catalyst, and optionally non-crosslinked polymer can be mixed at an elevated temperature to reduce the viscosity of the crosslinked polymer and increase the dynamic crosslinking reaction rate. For example, the mixture of the crosslinked polymer, catalyst, and non-crosslinked polymer can be subjected to a processing temperature higher than the processing temperature of the non-crosslinked polymer to form the polymer composition. That is, the mixture can be exposed to a temperature higher than either the melting point or the softening point of the non-crosslinked polymer. The temperature should be selected according to the requirements of the selected processing operation, as long as it does not exceed the decomposition temperature of the polymer. The softening point of the amorphous non-crosslinked polymer is determined by the Vicat method according to ASTM D-1525, and the melting point of the semi-crystalline non-crosslinked polymer is measured by DSC.

[0048] In one or more embodiments, the polymer compositions according to the present disclosure may be prepared using continuous or discontinuous extrusion, or with continuous or batch mixing. The process may use a single screw, twin screw, or multi-screw extruder, and in some embodiments may be used at temperatures ranging from 100°C to 270°C, and in some embodiments, from 140°C to 230°C. In some embodiments, the raw materials (crosslinked polymer, catalyst, and non-crosslinked polymer) are added to the extruder simultaneously or sequentially into a main feeder or a secondary feeder. In other embodiments, a kneader, calendar, or other internal mixer may be used.

[0049] A method of preparing a polymer composition according to the present disclosure may include the general steps of mixing a crosslinked polymer, a catalyst, and optionally a non-crosslinked polymer in an extruder; melt extruding the crosslinked polymer with a catalyst to form a dynamically crosslinked polymer, and optionally dispersing such dynamically crosslinked polymer within the non-crosslinked polymer; and forming pellets, filaments, or powder of the polymer composition.

[0050] Advantageously, the process of the present disclosure can be continuous such that the crosslinked polymer and catalyst can be constantly and continuously added to the process (e.g., at the first end of the extruder) and the formed polymer composition can be constantly and continuously formed at the end of the process (e.g., at the second end of the extruder). That is, additional crosslinked polymer and catalyst are added to the process (at the first end of the extruder) at the same time that the formed polymer composition from the process (at the second end of the extruder) is produced.

[0051] In one or more embodiments, the crosslinked polymer, particularly one obtained from scrap or molded parts, can be ground into smaller particles. It is contemplated that such size reduction may occur when extruding the crosslinked polymer with a catalyst in one or more embodiments. However, it is also contemplated that at least some of the size reduction may occur prior to grinding, milling, or otherwise chopping the larger scrap pieces into particles that can be easily fed into the extruder and / or have sufficient surface area to react with the catalyst and undergo dynamic crosslinking during the extrusion process. For example, after undergoing size reduction and dynamic crosslinking, the crosslinked polymer may have a particle size with a lower limit of any of 1, 5, 10, 15, 20, 30, 40, 50, or 100 microns, and an upper limit of any of 100, 500, 1000, 5000, 10000, or 100000 microns, where any lower limit may be used in combination with any upper limit.

[0052] In one or more embodiments, upon dynamic crosslinking, the time dependence of the storage modulus at temperatures above 90° C. shifts compared to the neat composition. The time dependence of the composition can be determined as the time at which the normalized relaxation reaches 1 / e relative to the initial value (G0, plateau modulus). The value of the normalized relaxation modulus can be obtained by exponential decay fitting to the storage modulus data. The plateau modulus corresponds to the fit at t=0 seconds, also referred to as G0.

[0053] Considering dynamic crosslinking, embodiments of the present disclosure also relate to reprocessing of crosslinked polymer (crosslinked polymer) compositions. In one or more embodiments, due to the inherent properties of the chemicals used, crosslinked polymer formulations can be reprocessed or recycled using similar processes applied to virgin polymers in the initial crosslinking process. Scrap or end-of-life parts undergo regrinding or other necessary processes to be able to provide material in the desired operation in a manner that is still useful as secondary raw material, with acceptable degradation of processability or properties. The objective is generally that the reprocessing parameters are similar to those used in the original manufacturing process. Advantageously, the polymer composition can be reprocessed and the properties of the polymer composition can be substantially maintained compared to those immediately before the reprocessing process. Specifically, in one or more embodiments, after the reprocessing process, the polymer composition maintains at least 40% of the plateau of the initial storage modulus above its melting temperature, as measured by dynamic mechanical analysis, compared to the polymer composition before the reprocessing process.

[0054] It is also contemplated that the reprocessing process may be repeated (through multiple cycles). In one or more embodiments, after repeated reprocessing, such as after 3 cycles of reprocessing or after 5 cycles of reprocessing, the polymer composition maintains at least 40% of its initial storage modulus plateau above its melt temperature as measured by dynamic mechanical analysis, compared to the polymer composition before the reprocessing process.

[0055] The polymer composition prepared by the method of the present invention may be in the form of granules that are applicable to various molding processes to produce manufactured articles, including injection molding, foaming, compression molding, steam chest molding, supercritical molding, additive manufacturing, etc.

[0056] In one or more embodiments, the polymer composition may be formulated as extruded filaments or granules (or pellets), which in some embodiments may be used in additive manufacturing processes.

[0057] In general, examples of commercially available additive manufacturing techniques include extrusion-based techniques such as fused filament fabrication (MJF), fused deposition modeling (FDM), or free forming, as well as other techniques such as electrophotography (EP), jetting, selective laser sintering (SLS), high speed sintering (HSS), powder / binder jetting (BJ), and vat photopolymerization. For each of these approaches, a digital representation of a 3D part is first sliced ​​into multiple horizontal layers. For each sliced ​​layer, a tool path is generated that provides instructions for a specific additive manufacturing system to print a given layer. Specific additive manufacturing techniques that may be particularly suitable for the polymer compositions of the present invention include, for example, fused filament fabrication and powder bed fusion (SLS, HSS, and BJ) techniques.

[0058] In fused filament manufacturing, an extrusion head heats a plastic filament to produce a polymer melt that is extruded through a nozzle in a controlled pattern onto a print substrate. The material is deposited to form a continuous layer. The filament can have a diameter of, for example, 1.0 to 4.0 mm, including filaments having diameters ranging from 1.5 to 3 mm, such as 1.75 mm or 2.85 mm.

[0059] Powder bed fusion techniques use powder materials in the build area instead of liquid or molten resin. For example, selective laser sintering (SLS) uses a laser to selectively sinter layers of powder, which sinters the material together. This process is then repeated layer by layer until the build is complete. Once the object is fully formed, it is left to cool in the machine before being removed. High speed sintering (HSS) is produced by depositing a thin layer of polymer powder, after which an inkjet printhead deposits an infrared (IR) absorbing fluid (or toner powder) directly onto the surface of the powder that needs to be sintered. The entire build area is then illuminated by an IR radiation source, such as an infrared lamp, causing the printed fluid to absorb the energy, which then melts and sinters the powder underneath. This process is then repeated layer by layer until the build is complete. While SLS and HSS are detailed as examples of powder bed fusion processes, the polymer composition can be adapted for use in other powder bed fusion processes, such as selective heat sintering (SHS), selective absorption sintering (SAS), selective inhibition sintering (SIS), and binder jetting. In such powder bed fusion processes, the polymer composition can be provided as a powder having an exemplary particle size distribution d50 in the range of 30-90 microns, d90 up to 150 microns, and d10 of at least 10 microns.

[0060] In one or more embodiments, the article is selected from the group consisting of shoe midsoles, hot melt adhesives, gaskets, hoses, cables, wires, sealing systems, conveyor belts, foxing tapes, NVH materials, soundproofing materials, roofing materials, and industrial flooring materials. In embodiments of multi-layer articles, it is contemplated that at least one of the layers comprises the polymer composition of the present disclosure.

[0061] As discussed above, articles formed from the polymeric compositions may have stress and elongation at break, hardness, compression set, impact strength, density, tear strength, elasticity, abrasion resistance, etc., that are comparable to articles formed from non-crosslinked polymers without the dynamically crosslinked polymer, i.e., the inclusion of the dynamically crosslinked polymer within a matrix of non-crosslinked polymer does not adversely affect the properties of the article.

[0062] For embodiments that are foam articles, such foam articles have a foam density of 0.2 to 0.6 g / cm according to ASTM D792. 3 Density in the range of, for example, 0.45 g / cm 3 Below, 0.43g / cm 3 Below, 0.42g / cm 3 Below, 0.41g / cm 3 Below 0.40g / cm 3 Below, 0.38g / cm 3 Below, 0.35g / cm 3 Below, 0.32g / cm 3 or less than 0.30g / cm 3 It may have the following densities:

[0063] The foamed article according to one or more embodiments of the present disclosure can have an Asker C hardness, as determined by JIS K7312, ranging from a lower limit of any of 15, 20, 25, 30, or 35 to an upper limit of 40, 45, 50, 55, or 60, where any lower limit can be combined with any upper limit.

[0064] A foam article according to one or more embodiments of the present disclosure may have a resiliency as determined by ASTM D2632 of at least 40%, at least 45%, at least 50%, at least 55%, at least 60%, at least 65%, or at least 70%.

[0065] The foam article according to one or more embodiments of the present disclosure may have a compressibility of 150 mm, as determined by ISO 4649:2017, measured with a load of 5 N. 3 Below, 140mm 3 Below, 130mm 3 Below, 120mm3 Below, 110mm 3 Below, 100mm 3 Below, 75mm 3 Below, 50mm 3 It may have the following wear:

[0066] The foamed article according to one or more embodiments of the present disclosure may have a shrinkage of 3% or less, 2.8% or less, 2.5% or less, 2.3% or less, or 2.0% or less, as determined by using the PFI method (PFI "Testing and Research Institute for the Shoe Manufacturing Industry" of Pirmesens-Germany) at 70°C for 1 hour.

[0067] The foamed article according to one or more embodiments of the present disclosure may have a compression set of less than 15%, less than 12%, less than 10%, or less than 8% as determined using Method B by ASTM D395 at 23° C., 25% strain, 22 hours.

[0068] The foamed article according to one or more embodiments of the present disclosure may have a compression set of less than 50%, less than 45%, less than 40%, or less than 35% as determined using Method B by ASTM D395 at 50° C., 50% strain, for 6 hours.

[0069] The foam article according to one or more embodiments of the present disclosure may have a tear strength, as determined by ASTM D624, of at least 3 N / mm, at least 3.5 N / mm, at least 4 N / mm, at least 4.5 N / mm, or at least 5 N / mm.

[0070] The foam article according to one or more embodiments of the present disclosure has a compressive strength of at least 2.5 N / mm2 as determined by ABNT-NBR 10456. 2 , at least 3.0N / mm 2 , at least 3.5N / mm 2 , at least 4.0N / mm 2 , or at least 4.5N / mm 2 The bond strength may be

[0071] For embodiments that are compact articles, one or more embodiments of the compact article may have a Shore A hardness in the range of 60-70, a breaking strength greater than 7 MPa, an elongation at break greater than 250%, and a compression set less than 35% according to NBR 13756-1996 (NBR 10025, Method B, 22 hours, 70° C.).

[0072] In one or more specific embodiments, the polymer composition can be used to form a shoe midsole, and the crosslinked polymer used to form the polymer composition can be EVA scrap, such as sprues, runners, flash, rejected parts, and the like, from the shoe midsole molding operation, which is ground or shredded. The ground EVA scrap can be mixed in an extruder with a catalyst and, optionally, with virgin EVA to form the polymer composition described herein. The polymer composition can then be used to form a shoe midsole. EXAMPLES

[0073] Test Method <Notched Izod impact resistance> Notched Izod impact testing was performed on a Ceast Resil 25 Digital Pendulum Unit, Model 6545, in accordance with ASTM D256: Standard Test Methods for Determining the Izod Pendulum Impact Resistance of Plastics, Method A. Pendulum Capacity: 2.0 Joules unless otherwise noted. Sample Size: Dimensions Notch Depth: 0.1 inches; Number of Specimens Tested per Sample Type: 5 (minimum); Test Temperature: Samples were at room temperature of 23°C during testing.

[0074] <Flexural modulus> Three point bend testing was performed on an Instron 3366 unit using Bluehill Universal software applying the principles of ASTM D790, Procedure A. ASTM D790, Procedure A - Flexural Properties of Unreinforced and Reinforced Plastics and Electrical Insulating Materials, Procedure A. Strain Rate: See results below, Crosshead Speed: See results below, Sample Size: 0.125" thickness x 5.0" length, Hold Spacing (Support Span): 2", Number of specimens tested per type: 5 at each strain rate, Test Conditions for Three Point Bend Test Results: Speed ​​0.05" / min, Span 2.0".

[0075] <Tensile properties> Tensile testing was performed on an Instron 3366 unit using Bluehill Universal software applying the principles of ASTM D638 Tensile Properties of Plastics. A 10 kN load cell was used. A long travel extensometer was used to determine strain values. Crosshead speed: 2.0 in / min, sample size: ASTM Type I dogbone, sample gauge length: 2.0 in.

[0076] <Dynamic mechanical analysis> Dynamic mechanical analysis was carried out using an Anton Parr MCR 501 equipped with a single cantilever fixture.

[0077] <Differential scanning calorimetry> To illustrate the formation of dynamic crosslinked networks, the thermal response was measured by a differential scanning calorimeter (DSC) TA Instruments Q200 instrument.

[0078] DSC method: In the first heating step, the sample was heated to 160°C at a heating rate of 10°C / min. The temperature was kept constant at 160°C. The sample was then cooled to -20°C at a rate of 10°C / min and equilibrated at -20°C for 1 min. In the second heating step, the sample was heated to 160°C at a heating rate of 10°C / min, held at 160°C for 1 min, and then cooled to 30°C at a rate of 10°C / min.

[0079] Shear Rheology The shear rheology tests were performed in the following order: first a frequency sweep, immediately followed by a time sweep, and then another frequency sweep. Comparisons were performed between samples after different thermal cycles and at different frequencies to understand the possible effect of the catalyst on the polymer composition. All tests were performed in a TA Instruments Dynamic Shear Oscillatory Rheometer DHR3 with a 25 mm diameter, 1 mm gap parallel plate accessory in a nitrogen (N2) atmosphere at 170°C.

[0080] Test conditions - First: Frequency sweep from 628.32 to 0.75 rad / s, deformation within the Linear Viscoelastic Region (LVR). Time sweep was performed at 1 rad / s in the LVR for 60 minutes. Second frequency sweep was performed from 628.32 to 0.06 rad / s in the LVR.

[0081] Stress relief Stress relaxation measurements were performed using an Ares G2 rheometer equipped with a 25 mm parallel plate fixture. The gap was set at 1.5 mm. The strain was set at 1% (within the linear range). An axial force of 5 N was applied. Tests were performed on each sample at each of four temperatures (100°C, 120°C, 150°C, and 170°C).

[0082] Melting / mixing crushed EVA scrap with EVA and dynamic crosslinking agent Elastomeric networks were prepared by reactive extrusion of ethylene vinyl acetate copolymer (EVA) with ground EVA scraps spiked with zinc / carboxylate. Conventional EVA (Braskem commercial grade HM728, VAc content 28%, melt index (190°C / 2.16 kg = 6 g / 10 min) was melted / mixed with ground peroxide crosslinked EVA scraps and zinc dicarboxylate in a Theysohn TSK 21 mm twin screw extruder. Extrusion conditions and mechanical properties are summarized in Tables 2 and 3, respectively.

[0083] Crosslinked EVA scrap foam was obtained from a commercial midsole manufacturer and ground to form particulates using an extruder operating at 190°C.

[0084] A typical midsole composition includes EVA polymer, an inorganic salt such as CaCO3 (1-5% by weight), a blowing agent such as azodicarbonamide (2-3% by weight), and a dicumyl peroxide curing agent (0.5-2% by weight). The particle size distribution of the ground scrap was measured by laser diffraction using a Malvern Mastersizer instrument. The average particle size was approximately 300 microns.

[0085] Examples 1 and 2 show EVA extruded with ground EVA scrap without the addition of a dynamic crosslinker. Examples 2 and 3 show the effect of extruding zinc diacrylate with a mixture of EVA and ground EVA scrap. Examples 4 and 5 show the effect of extruding zinc acetyl acetate with a mixture of EVA and ground EVA scrap.

[0086] [Table 1]

[0087] [Table 2]

[0088] The resulting extruded mixture was cooled in a water bath and collected as pellets. A subset of the pelletized samples was dried in a convection oven at 60° C. for at least 8 hours and then molded according to ASTM methods to produce test specimen bars. Mechanical properties were measured using ASTM procedures and the results are reported in Table 3.

[0089] The fact that the compositions of the present invention were readily processed using conventional (standard) injection molding techniques for thermoplastics indicates their melt processability.

[0090] [Table 3]

[0091] dynamic mechanical analysis To demonstrate the formation of an elastomeric network when EVA was mixed with Zn / carboxylate, dynamic mechanical analysis was performed on molded plaques (17.5 mm x 13.95 mm x 1.5 mm) using a single cantilever geometry. The samples were equilibrated at 150°C for 5 minutes and then the temperature was increased to 50°C at 3.00°C / min.

[0092] As shown in Figures 1-3, the storage modulus and tan δ values ​​observed in the temperature range of 15-30°C clearly demonstrate that the addition of zinc carboxylates to EVA increases the elastomeric response. The modulus values ​​at 25°C are reported in Table 4 below.

[0093] [Table 4]

[0094] Differential scanning calorimetry To further explain the formation of elastomeric networks when EVA is blended with Zn / carboxylate, DSC was used to measure the thermal response of EVA scrap blends after reactive extrusion. Melting curves are reported for the second melt after heating and cooling cycles according to Figure 4. The melting peaks for all blends containing EVA scrap are similar to the melting curve for the EVA control sample. The inclusion of 30% scrap results in a broader peak but does not significantly shift the peak melting temperature.

[0095] The cooling curve of the sample containing ground EVA scrap, shown in FIG. 5, shows two distinct crystallization peaks, one at the same temperature as the EVA control and one at a higher temperature that can be attributed to the ground scrap.

[0096] When zinc diacrylate or zinc acetylacetonate are extruded with ground scrap and EVA, the lower temperature crystallization peak shifts significantly to lower temperatures. Unblended EVA HM728 has a Tc peak at about 54°C, and ground scrap blended EVA has a Tc peak at about 52°C. Samples extruded with zinc diacrylate or zinc acetylacetonate have a Tc peak at about 43°C (a shift of nearly 10°C). This shift suggests crosslinking of the EVA / scrap blends when extruded with either Zn diacrylate or Zn acetylacetonate.

[0097] Shear Rheology Small angle oscillatory shear (SAOS) was used to measure the viscoelastic response at higher temperatures, as shown in Figures 6-9. At 170 °C, the sample containing Zn-diacrylate, shown in Figure 7, exhibited a significantly lower crossover frequency than the sample containing only scrap, shown in Figure 6. The sample containing Zn-diacrylate also exhibited a significantly lower tan δ peak than the sample containing only scrap, as shown in Figure 9. These observations indicate elastomeric behavior well above the melting point of EVA, indicating that a crosslinked network is formed.

[0098] Stress / Relaxation Measurements To demonstrate that the networks of the present invention are dynamically crosslinked and therefore capable of changing morphology in response to a stimuli such as increased temperature, stress relaxation measurements were performed.

[0099] The samples tested were compositions of the present invention described above in Examples 2, 4, and 6.

[0100] The stress relaxation results shown in Figures 10, 11, and 12 show that the storage modulus (G') is time dependent at each temperature tested. For each material of the invention, G'=G'(t), and the value of G'(t) drops to less than 50% of G(t=0) within 10,000 seconds for each EVA / scrap composition. The value of G(t=0) was obtained by exponential decay fitting to the data. The relaxation modulus corresponds to the fit at t=0 seconds, also referred to as G0.

[0101] Reprocessing Test To demonstrate that the compositions of the present invention can be reprocessed by heating and melting, the extruded pellets were pressed multiple times in a Carver press using the conditions listed in the table below. The pellet samples were pressed between steel plates using a 0.6 mm thick brass die to control the thickness of the sample. After the first pressing step, the film was cooled, cut into pieces, and pressed again to form a second film. The second film was cut into pieces and pressed to form a third film. After each pressing, a sample of the film was collected for dynamic mechanical analysis.

[0102] [Table 5]

[0103] The inventive samples produced a smooth, uniform film after each press, demonstrating that the composition flows and takes the shape of the mold.

[0104] The viscoelastic response of the pressed films was measured by dynamic mechanical analysis (DMA) temperature sweep using a TA Instruments rheometer equipped with a tension fixture. Sample dimensions were 0.6 mm thick, 7 mm wide, and 22-26 mm long. The strain amplitude was 15 microns, the frequency was 1 Hz, and the heating rate was 3°C / min.

[0105] The elastic modulus and storage modulus values ​​are reported as a function of temperature. As shown in Figures 13-15, the compositions of the present invention exhibit a plateau storage modulus over a temperature range of about 20°C to about 80°C. After three processing steps, the plateau modulus of the compositions of the present invention retains at least half of its initial value, designated E' after the first press.

[0106] Although only a few example embodiments have been described in detail above, those skilled in the art will readily appreciate that many modifications are possible in the example embodiments without substantially departing from the present invention. Accordingly, all such modifications are intended to be included within the scope of the present disclosure as defined by the claims. In the claims, means-plus-function clauses are intended to cover the structures described herein as performing the recited functions, and structural equivalents as well as equivalent structures. Thus, while nails and screws may not be structurally equivalent in that nails use cylindrical surfaces to fasten wooden parts while screws use helical surfaces, in the context of fastening wooden parts, nails and screws may be equivalent structures. It is the express intent of the applicants not to rely on 35 USC Section 112(f) for any limitation of any claim, except to the extent that the claim expressly uses the phrase "means for" with the relevant function.

Claims

1. 1. A method comprising: processing a crosslinked polymer and a catalyst to form a dynamically crosslinked polymer during a melt processing operation, said crosslinked polymer comprising at least one monomer selected from vinyl esters, C2 to C12 olefins, and combinations thereof.

2. 1. A method comprising mixing a crosslinked polymer, a catalyst, and a non-crosslinked polymer at a temperature above a processing temperature of the non-crosslinked polymer to form a polymer composition, comprising: each of the crosslinked polymer and the non-crosslinked polymer comprises at least one monomer selected from vinyl esters, C2 to C12 olefins, and combinations thereof; and The method, wherein the crosslinked polymer is present in an amount of at least 15% by weight based on the total of the crosslinked polymer and the non-crosslinked polymer.

3. 3. The method of claim 1 or 2, wherein the crosslinked polymer is pre-processed and / or the non-crosslinked polymer is virgin polymer.

4. 4. The method of claim 2 or 3, wherein the polymer composition comprises a matrix phase of a non-crosslinked polymer and a dispersed phase of a dynamically crosslinked polymer.

5. The method of any one of claims 1 to 4, wherein the crosslinked polymer is an ethylene vinyl acetate copolymer.

6. 6. The method of claim 5, wherein the ethylene vinyl acetate has a melt flow in the range of 0.1 to 300 g / 10 min, measured according to ASTM D1238 at 190° C. and 2.16 kg, and / or the ethylene vinyl acetate copolymer has a vinyl acetate content in the range of 5 to 80% by weight, and / or the crosslinked polymer has a particle size in the range of 1 to 100,000 microns, preferably 5 to 100 microns.

7. The method of any one of claims 2 to 6, wherein the non-crosslinked polymer is an ethylene vinyl acetate copolymer.

8. The method of any one of claims 2 to 6, wherein the non-crosslinked polymer is a terpolymer of ethylene, vinyl acetate, and a branched vinyl ester.

9. 9. The method of any one of claims 1 to 8, wherein the catalyst is a metal salt selected from the group consisting of metal salts, metal oxides, metal alkoxides, metal acrylates, metal acetylacetonates, metal hydrides, metal halides, and metal hydroxides.

10. The method of any one of claims 1 to 9, wherein the catalyst is selected from borates, diamines, diols, diacids, dianhydrides, and combinations thereof.

11. 11. The method of any one of claims 1 to 10, further comprising the step of grinding the crosslinked polymer prior to said mixing and / or adding to the polymer composition at least one additive selected from the group consisting of fillers, fibers, elastomers, plasticizers, processing aids, mold release agents, lubricants, dyes, pigments, antioxidants, light stabilizers, and flame retardants.

12. The method according to any one of claims 1 to 11, further comprising the steps of mixing the polymer composition with a blowing agent, an accelerator and a curing agent, foaming the polymer composition and / or subjecting the polymer composition to a molding operation preferably selected from the group consisting of injection molding, compression molding, steam chest molding, supercritical foaming and additive manufacturing.

13. The method of any one of claims 1 to 12, further comprising the step of extruding the polymer composition as filaments having a diameter in the range of 1.5 to 3 mm or as pellets.

14. A thermoplastic polymer composition produced by the method of any one of claims 1 to 13, optionally comprising the time dependence of the storage modulus at temperatures above 90° C. is shifted relative to the neat composition; and / or The thermoplastic polymer composition comprises A matrix phase of a non-crosslinked polymer; and A dynamically crosslinked polymer comprising a crosslinked polymer and a catalyst dispersed in the matrix phase.

1. A thermoplastic polymer composition comprising:

15. 15. An article comprising the thermoplastic polymer composition of claim 14.

16. the article is selected from the group consisting of shoe midsoles, hot melt adhesives, gaskets, hoses, cables, wires, sealing systems, conveyor belts, foxing tapes, NVH materials, soundproofing materials, roofing materials, and industrial flooring materials; and / or the molded article has a density in the range of 0.1 to 0.4 g / cc; and / or the article has equivalent stress and elongation at break, hardness, compression set, impact strength, density, tear strength, elasticity, abrasion resistance to a reference article formed from a non-crosslinked polymer without the dynamically crosslinked polymer; and / or the article has a Shore A hardness in the range of 60 to 70, a breaking strength of greater than 7 MPa, an elongation at break of greater than 250%, a compression set of less than 35% (NBR 10025, Method B, 22 hours, 70° C.) (according to NBR 13756-1996); 16. The article of claim 15.

17. A method for producing a printed article comprising the steps of sequentially printing layers of the polymer composition of claim 14.

18. The sequential printing is Depositing a layer of powder comprising a polymer composition on a surface of a target object; and melting and sintering the polymer composition; Contains, or The sequential printing is depositing sequentially layers of a molten polymer phase, said molten polymer phase comprising said polymer composition, and optionally melting polymer filaments comprising said polymer composition to form a molten polymer phase; 20. The method of claim 17.

19. 19. An article formed by the method of claim 17 or 18.

20. 1. A method for reprocessing a polymer composition, comprising:

15. The method of claim 14, further comprising the step of: reprocessing the polymer composition of claim 14 at a temperature above the melting or softening temperature of the thermoplastic polymer, wherein after the reprocessing, the polymer composition maintains at least 40% of its initial storage modulus plateau above its melting temperature as measured by dynamic mechanical analysis compared to the polymer composition before the reprocessing; The method further optionally includes repeating said processing at least two additional times, wherein after said repeated reprocessing, the polymer composition maintains at least 40% of its initial storage modulus plateau above its melt temperature as measured by dynamic mechanical analysis, compared to the polymer composition before the reprocessing.